Optimizing the Role of Posyandu and Posbindo Cadres in Alleviating Stunting and Preventing Non-Communicable Diseases in Pacar Kembang Village, Surabaya - Anik Handayati; Pestariati Pestariati; Suhariyadi Suhariyadi (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2026)
Stunting, a significant health problem in Indonesia, must be addressed. Stunting is defined as a condition caused by inadequate nutritional intake that does not meet nutritional needs. Integrated Service Posts (Posyandu) are a way to provide health services to the community and have the ability to develop resources, especially in health matters. The methods used in this community service activity are lecture/presentation and discussion and question and answer methods. The lecture activities included presenting material on the importance of balanced nutrition during the first 1000 days of life (HPK), explaining the role of cadres in providing simple counseling to the community, facilitating discussions and question-and-answer sessions, and concluding the session. Overall, the implemented activities showcase the active participation of both the cadres and the community. These results serve as the basis for implementing further activities in the form of monitoring, evaluation, and more targeted health interventions.